The adventures of Sherlock Holmes - Doyle, Arthur Conan, Sir, 1859-1930 (Scholastic classics, 2003)
A collection of Sherlock Holmes mystery adventures, including "A Scandal in Bohemia," "The Red-headed League," and "The Speckled Band."